Features of Display Emotional Deprivation in Interpersonal Relations at Children of Preschool Age - Yakubova, Guzal (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Article is devoted to the content of deprivation. The emergence of deprivation considered in psychological research. And also article about results of the scientifically research influence emotional deprivation to development of child under school age as subject of the social relations.